Keadilan dan Etika dalam Kebijakan Pertambangan: Inkonsistensi Hukum Pemberian Konsesi Tambang pada Ormas Keagamaan - Noor, Muhammad (Asian Journal of Law and Humanity, 2025)
Mining concession policies in Indonesia face serious challenges due to inconsistent norms, which are now complicated by profound ethical dimensions. This study analyses the vertical inconsistency between Government Regulation No. 25 of 2024, which prioritises mining concessions for religious organisations, and Law No. 3 of 2020, which limits such rights to state-owned enterprises, regional-owned enterprises, and private enterprises. Using normative legal research methods, the results of the study show that Article 83A paragraph (1) of PP No. 25 of 2024 adds a new norm that substantially contradicts the above law. More than just a legal issue, this policy raises crucial ethical questions. From an ethical perspective, granting this permit creates a conflict of interest for organisations that have historically played a role as moral and social guardians. The potential for abuse of authority and corruption also increases, undermining the principle of transparency. Furthermore, there are ethical concerns regarding the capacity and readiness of CSOs to manage extractive industries that pose high risks to the environment and society. Therefore, legal harmonisation is needed that not only guarantees certainty and justice, but also considers the broader ethical implications in order to prevent adverse social and environmental impacts.